Development and testing of the Prev'Quedas game for older adults in the community: a descriptive study - Jamylle Lucas Diniz; Janaína Fonseca Victor Coutinho; Marília Braga Marques; Ismayle de Sousa Santos; Rachel Gabriel Bastos Barbosa; Rávida da Rocha Lima Silva; Débora dos Reis Soares Ferreira; Maria Júlia Barbosa Muniz (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to develop and test a board game for fall prevention in older adults in the community. Methods: a descriptive study, carried out through the use of game design elements (narrative, mechanics, aesthetics and technology), the Health Promotion Model, assessment by experts and testing with older adults. For assessment, the Concordance Index was used, considering it greater than 80%. Results: three prototypes and the final version were developed. The game's narrative was based on promotion model, comprising individual aspects, benefits and barriers in behavior to prevent falls. The mechanics outlined goals and rules. Aesthetics encompassed layout and illustrations. The technology involved board, cards, pin, roulette and instruction manual. The game was assessed by 36 experts and 31 older women from the community, with a Concordance Index of 93.22% and 99%, respectively. Conclusions: the game developed and tested was considered an adequate educational strategy for fall prevention.